The German block of the ESCB multi-country model - Igor Vetlov; Thomas Warmedinger (European Central Bank (ECB), 2006)
The paper presents the German block of the ESCB multi-country model. It builds on previous modelling work on the Area Wide Model and other country blocks of the ESCB multicountry-model. Whilst being analogous to these models in following a common modelling approach and the same theoretical framework, the German model has also some unique features for instance with regard to the modelling of the investment components, imports and employment. The paper provides a brief overview of the theoretical framework of the model, its estimation results, and a discussion of the dynamic model properties. The model is primarily used for preparing quarterly projections for the German economy as well as for policy analysis.
Keywords: C3; C5; E1; E2; 330; Germany; Macro-econometric Modelling; Makroökonometrie; Wirtschaftsprognose; Simulation; Zentralbank; EU-Staaten; Deutschland